Partisipasi Masyarakat Sekitar Desa Penyangga Terhadap Fungsi Ekologi Pengelolaan Taman Nasional Alas Purwo: Community Participation Around Buffer Village in the Ecological Function of Alas Purwo National Park Management - Eko Setiawan (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
The existence of communities around conservation areas has an important role for the preservation of Alas Purwo National Park. Buffer villages have a function to maintain the integrity of conservation areas from all forms of disturbances, originating from outside or within the area that can result in changes in the integrity and function of the national park area. The effectiveness of conservation area management will be disrupted if the participation rate is low. This study aims to determine the form of behavior of the peyangga village community and its interaction with conservation areas. Qualitative descriptive research approach and purposive determination of research locations. Data collection methods through interviews and observations. Data analysis starts from data collection, data reduction, data presentation, and drawing conclusions. To explain the phenomenon raised by the researcher, using the theory of structural functionalism. According to this theory society as a social system consists of interrelated parts or elements in equilibrium. Changes that occur in one part will bring about change, against another. The results showed that collaborative management of conservation areas by involving the participation of local communities has an important meaning. Through this activity, it can increase public awareness so that it can play a maximum role in the management of conservation areas.